2016
DOI: 10.7717/peerj.1952
|View full text |Cite
|
Sign up to set email alerts
|

De novogenome assembly ofGeosmithia morbida, the causal agent of thousand cankers disease

Abstract: Geosmithia morbida is a filamentous ascomycete that causes thousand cankers disease in the eastern black walnut tree. This pathogen is commonly found in the western U.S.; however, recently the disease was also detected in several eastern states where the black walnut lumber industry is concentrated. G. morbida is one of two known phytopathogens within the genus Geosmithia, and it is vectored into the host tree via the walnut twig beetle. We present the first de novo draft genome of G. morbida. It is 26.5 Mbp i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The G. morbida genome (26.5 Mbp) has recently been sequenced, revealing less than 1% repetition within its more than 6000 genes [35]. A genome-enabled research approach focused on G. morbida can provide a better understanding of the biology of the pathogen involved in TCD and identify candidate genes and functions required for pathogenesis.…”
Section: The Plant Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The G. morbida genome (26.5 Mbp) has recently been sequenced, revealing less than 1% repetition within its more than 6000 genes [35]. A genome-enabled research approach focused on G. morbida can provide a better understanding of the biology of the pathogen involved in TCD and identify candidate genes and functions required for pathogenesis.…”
Section: The Plant Pathogenmentioning
confidence: 99%
“…Without an insight into the pathogenicity and mechanisms by which G. morbida overcomes walnut defenses, our ability to predict, prevent, and manage TCD epidemics will be extremely limited. Thus, additional genomic research based on Schuelke et al will serve as a valuable tool for further investigation into the pathogenesis of G. morbida and related forest diseases [35].…”
Section: The Plant Pathogenmentioning
confidence: 99%
“…To date, the i5K Workspace has supported publication of seven insect genomes that were manually curated with Apollo (11)(12)(13)(14)(15)(16)(17). Other projects that have used Apollo include genomes of additional insects (18)(19)(20), human parasites (21)(22)(23), birds (24,25), the sea lamprey (26), plants (27)(28)(29), fungi (30)(31)(32)(33)(34)(35) and a plant pathogenic nematode (36). Projects such as the re-annotation of the whipworm genome by hundreds of high school students in the UK, supported by the Institute for Research in Schools (IRIS) (37), and the curation of 33,044 gene loci in the kiwifruit genome by 93 annotators, are evidence of Apollo's robust support for large dispersed projects.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a reference genome of Geosmithia morbida that consisted of 73 scaffolds totaling 26.5 Mbp in length (Schuelke et al , 2016). This genome represents one of the smaller fungal tree pathogen genomes reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Genome expansions were associated with parasitism in general and increased pathogenicity and virulence in several fungal lineages (Spanu et al , 2010). Previous genome sequencing of Geosmithia morbida (Schuelke et al , 2016) showed that this newly emerged fungal pathogen has a smaller genome than several of its closely related nonpathogenic relatives in the Hypocreales. Hence, Geosmithia has taken an evolutionary path to pathogenicity that has not been characterized previously in plant-associated fungi.…”
Section: Introductionmentioning
confidence: 99%